2016
DOI: 10.1017/jsl.2015.11
|View full text |Cite
|
Sign up to set email alerts
|

Linear Orders Realized by C.E. Equivalence Relations

Abstract: Let E be a computably enumerable (c.e.) equivalence relation on the set ω of natural numbers. We say that the quotient set ω/E (or equivalently, the relation E) realizes a linearly ordered set L if there exists a c.e. relation respecting E such that the induced structure (ω/E; ) is isomorphic to L. Thus, one can consider the class of all linearly ordered sets that are realized by ω/E; formally, K(E) = {L | the order-type L is realized by E}. In this paper we study the relationship between computability-theoret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…As we mentioned, Malcev [20] and Rabin [23] initiated this line of research, and their work lead to the modern development of the theory of computable structures [12]. Recently, the third approach has been suggested that introduces effectiveness into the study of infinite algebraic structures [2] [3] [8]. In this approach the primary objects are domains of the type ω/E, where E is an equivalence relation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we mentioned, Malcev [20] and Rabin [23] initiated this line of research, and their work lead to the modern development of the theory of computable structures [12]. Recently, the third approach has been suggested that introduces effectiveness into the study of infinite algebraic structures [2] [3] [8]. In this approach the primary objects are domains of the type ω/E, where E is an equivalence relation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, such domains do not realise infinite complete graphs. In [8], it is proved that there are domains that realise linear orders of the type ω + 1 + ω only, where ω is the order of negative integers. These all show that some domains allow us to tame algebraic structures.…”
Section: Discussionmentioning
confidence: 99%
“…Additional interest for computable reducibility on ceers comes from the study of c.e. presentations of structures, as is shown for instance in [12,16]. It is also worth noticing that ceers have been investigated in computability theory also not in connection with computable reducibility: for instance, Carroll [7] studied the lattice of ceers under inclusion; Nies [26] studied ceers modulo finite differences: they both showed that the first order theory of the resulting structures is computably isomorphic to Th 1 pNq.…”
Section: Introductionmentioning
confidence: 97%
“…Given a ceer E (having possibly some interesting computational property) it is natural to ask which algebras scriptA can be positively presented having E as their equality relation =A (cf., e.g., [19, 22]). Surprisingly, much less is known about the reverse problem, namely, given a class of structures frakturC, which ceers are “realized” by members of frakturC?…”
Section: Introductionmentioning
confidence: 99%